Fabrication of porous collagen scaffold for cardiovascular engineering - Song, Sin Nee. (2008)
Freeze-drying technique was employed to fabricate a porous collagen scaffold to explore its application in the tissue-engineering of cardiovascular system. The effect of thermal conductivity of mold materials and freezing kinetics on the pore structure of the scaffold was investigated. The influence of dehydrothermal (DHT) process, 1 -ethyl-3-(3-dimethyl aminopropyl)carbodiimide / N-hydroxysuccinimide (EDC/NHS) and glutaraldehyde (GA) cross-linking on the mechanical property was also studied.